Laparoscopic vs. open anatomical hepatectomy for intrahepatic cholangiocarcinoma: A retrospective cohort study - Wang, Jianlei; Ma, Delin; Du, Gang; An, Baokun; Xia, Tong; Zhou, Tao; Sun, Qingmei; Liu, Fengyue; Wang, Yadong; Sui, Deling; Zhai, Xiangyu; Jin, Bin (Frontiers in Surgery, 2022)
Abstract Background Intrahepatic cholangiocarcinoma is a highly malignant and invasive cancer originating from biliary epithelial cells. The current study was designed to evaluate the feasibility, safety, and clinical outcomes of laparoscopic anatomical hepatectomy in patients with intrahepatic cholangiocarcinoma. Methods After screening, 95 patients who underwent anatomical hepatectomy for intrahepatic cholangiocarcinoma at our center were enrolled and divided into two groups according to the surgical approach; the baseline characteristics, pathological findings, surgical outcomes, and long-term outcomes were compared. Moreover, univariate and multivariate analyses were performed to identify independent prognostic factors for overall survival (OS) and disease-free survival (DFS). Results There were no significant differences in baseline characteristics or pathological findings between the two groups. Regarding short-term outcomes, the intraoperative blood loss, incision length, and length of postoperative hospital stay were more favorable in the laparoscopic anatomical hepatectomy group than the open anatomical hepatectomy group (P<0.05). The two groups differed significantly in the extent of liver resection, with a lower lymph node dissection rate and lymph node yield in the laparoscopic anatomical hepatectomy group (P<0.05). Furthermore, the postoperative complication rate was similar in the two groups (P>0.05). The median postoperative follow-up times were 10.7 and 13.8 months in the laparoscopic anatomical hepatectomy and open anatomical hepatectomy groups, respectively. Regarding the long-term follow-up results, OS and DFS were similar in the two groups (P>0.05). On multivariate analysis, the independent prognostic factors for OS were CA-199, CEA, HGB, tumor diameter, and T stage, and those for DFS were CA-199 (P<0.05), and T stage (P<0.05). Conclusion laparoscopic anatomical hepatectomy for intrahepatic cholangiocarcinoma is safe and feasible when performed by experienced surgeons. Compared with open anatomical hepatectomy, laparoscopic anatomical hepatectomy provides better short-term outcomes and a comparable long-term prognosis.